PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Jufrizen Jufrizen (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
The results showed that compensation had no significant effect on organizational commitment at PT Perkebunan Nusantara III (Persero) Medan. Career development has no significant effect on organizational commitment at PT Perkebunan Nusantara III (Persero) Medan. Compensation does not significantly influence the job satisfaction of employees at PT Perkebunan Nusantara III (Persero) Medan. Career development and a significant positive effect on job satisfaction of employees at PT Perkebunan Nusantara III (Persero) Medan. Job satisfaction does not significantly influence organizational commitment at PT Perkebunan Nusantara III (Persero) Medan. Keywords: Compensation, Career Development, Job Satisfaction, Organizational Commitment